2014
DOI: 10.1210/me.2013-1340
|View full text |Cite
|
Sign up to set email alerts
|

Human Endometrial DNA Methylome Is Cycle-Dependent and Is Associated With Gene Expression Regulation

Abstract: Human endometrium undergoes major gene expression changes, resulting in altered cellular functions in response to cyclic variations in circulating estradiol and progesterone, largely mediated by transcription factors and nuclear receptors. In addition to classic modulators, epigenetic mechanisms regulate gene expression during development in response to environmental factors and in some diseases and have roles in steroid hormone action. Herein, we tested the hypothesis that DNA methylation plays a role in gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
80
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(93 citation statements)
references
References 104 publications
10
80
2
Order By: Relevance
“…In addition, estrogen and progesterone treatment in human endometrial stromal cell cultures decreased DNMT3a and DNMT3b mRNA expression [12]. The DNA methylation status of many genes in the endometrium changes between the proliferative and mid-secretory phases [13]. These findings suggest that histone modifications and DNA methylation are involved in the regulation of gene expression of human endometrial stromal cells undergoing decidualization.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, estrogen and progesterone treatment in human endometrial stromal cell cultures decreased DNMT3a and DNMT3b mRNA expression [12]. The DNA methylation status of many genes in the endometrium changes between the proliferative and mid-secretory phases [13]. These findings suggest that histone modifications and DNA methylation are involved in the regulation of gene expression of human endometrial stromal cells undergoing decidualization.…”
Section: Introductionmentioning
confidence: 93%
“…This suggests that decidualization did not remarkably change the DNA methylation status in human endometrial stromal cells. Recently, Houshdaran et al [13] compared DNA methylation status of the endometrial tissues between proliferative and mid-secretory phases using an Illumina Infinium HumanMethylation 27 BeadChip that covers DNA methylation in 27,000 CpG sites of the promoter region around the TSS. In that study, the cut-off value of the difference of DNA methylation rate between the two groups was set at 13.5 %, and only 67 differentially methylated CpG sites were identified.…”
Section: Dna Methylation During Decidualizationmentioning
confidence: 99%
“…[Houshdaran et al 2014]. Shift in methylation of two isoforms of transcription factor GATA (GATA2 and GATA6) results in impairment of hormonal sensitivity and aberrant expression of many candidate EM genes [Dyson et al 2014].…”
Section: Epigenetic Regulation Of Emmentioning
confidence: 99%
“…During the secretory phase, including the implantation window and decidual transformation, the expression profiles of endometrial genes are changed considerably compared to proliferative phase [5][6][7][8]. It has been suggested that abnormalities in gene expression during the secretory phase may lead to inappropriate endometrial development and, consequently, various reproductive disorders, including recurrent spontaneous abortion [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%